LANGUAGE, POWER, AND IDEOLOGY: DEVELOPING CRITICAL READING SKILLS THROUGH ANIMAL FARM - Astuti, Aura; Widjajanti, Suzanna; Ayubadiah, Fitrahnanda (Prologue: Journal on Language and Literature, 2025)
The increasing manipulation of language in political discourse has renewed academic interest in how power and ideology are embedded in everyday texts—a concern particularly urgent in today's post-truth era. In response, this study investigates how the theoretical foundations of Critical Discourse Analysis (CDA) are principally informed by the seminal frameworks advanced by scholars such as Norman Fairclough and Teun A. van Dijk can serve as valuable foundations for enhancing critical reading abilities in higher education. CDA theorizes language functions not as a neutral conduit but as a socially embedded practice that simultaneously mirrors and perpetuates existing power relations. Through a classroom-based analysis of George Orwell’s Animal Farm, this study operationalizes CDA as both an analytical and pedagogical framework. Students used AntConc, a corpus analysis tool, to examine rhetorical patterns, slogans, and ideological shifts in the text. The application of CDA enabled learners to uncover how language constructs dominance, distorts ideology, and silences dissent. Key features of CDA—such as intertextuality, hegemony, and discursive strategies—were translated into student-friendly tools for critical textual engagement. The findings suggest that integrating CDA with literary analysis not only enhances students’ interpretive depth but also cultivates their political literacy.